Studies developed based on the “index for inclusion” document - Menino-Mencia, Gislaine Ferreira [UNESP]; Belancieri, Maria de Fátima; Dos Santos, Mônica Pereira; Capellini, Vera Lucia Messias Fialho (FapUNIFESP (SciELO), 2019)
Inclusion in Education as a new proposal of school culture aims at the development of a school “for all”. The implications of this legal process consist of the recognition of equal value and rights among human beings and the consequent decision-making by the school, with a view to developing inclusive cultures, policies and practices. One of the possibilities of carrying this task out is through the development of the Index for Inclusion. It is a guiding document of institutional processes of self-revision, particularly directed to schools of Basic Education, but quite adaptable to other educational contexts and even to other types of institution. Thus, the objective of this study was to carry out a theoretical review on the theoretical and methodological construction and the applicability of the document “Index for Inclusion”. Characterized as a narrative bibliographic study, data collection was carried out in national and international databases, such as Web of Science, Scopus, Parthenon, Capes and Dialnet, through the use of the following keywords: “Index for Inclusion” and “Booth”, with a temporary cutoff between the years 2011 and 2016, resulting in 17 papers. In addition to the dissemination of the use of the instrument, this study shows how the “Index for Inclusion” has been adapted and developed in the international and national educational context, enabling the Brazilian public network of schools to have greater autonomy when it comes to inclusive cultures, policies and practices.
Estudos desenvolvidos tendo como base o documento “index para a inclusão”
Keywords: Inclusive Education; Index for Inclusion; Special Education